The Use of Therapeutic Drug Monitoring to Personalize Once-daily Intravenous Busulfan in Thai Pediatric Patients Underwent Hematopoietic Stem Cell Transplantation - Ratanatharathorn, Cholada; Meeudompong, Utairat; Ratanatharathorn, Cholatid; Sanpakit, Kleebsabai (Siriraj Medical Journal, 2025)
Objective: Therapeutic drug monitoring (TDM) for personalizing busulfan dosing in pediatric hematopoietic stem cell transplantation (HSCT) is recommended. The proportion of patients requiring dose adjustments and the frequency of achieving the target area under the time curve (AUC) was observed. Materials and Methods: This study included children who underwent once-daily intravenous busulfan-conditioning HSCT during October 2020 to April 2024. The initial busulfan dosage followed the European Medicines Agency nomogram, set between 3.2 and 4.8 mg/kg/day. Blood samples were collected to analyze pharmacokinetics and calculate AUC. Dose adjustments were made if AUC fell outside the target of 3,600 to 6,000 μMolar·min. Results: The study comprised 26 children. Dose adjustments for busulfan were performed in 17 patients (65.4%). Individual average AUCs ranged from 2,566.2 to 6,943.05 μMolar·min. Patients under 10 years had a higher likelihood of an out-of-range target AUC following dose adjustment compared to those aged ≥ 10 years (43.8% and 0%, respectively; P=0.023). A lower-than-target average AUC was significantly related to an earlier disease relapse compared to non-lower range AUCs (P<0.005). Conversely, higher AUCs did not correlate with busulfan-related side effects or treatment-related mortality. Conclusion: Our findings support TDM as a strategy to enhance the efficacy of once-daily intravenous busulfan in HSCT among Thai pediatric patients. TDM may help reduce the frequency of subtherapeutic exposures, which is associated with disease relapse. Patients under 10 years face more difficulties in achieving the target AUC, indicating the need for careful monitoring and dose adjustments in this age group.